Estudio de mercado emisor en el consumo de turismo de crucero en el destino Manta - Mejía Cano, Yelixsa (2019)
The objective of this research was to carry out a study of the issuing market for cruise tourism consumption in the destination of Manta. This research is quantitative and employs deductive and inductive and exploratory methods; a methodology consisting of four phases was used: An analysis of the evolution of the cruise industry in the destination Manta identified historical, geophysical and tourist characteristics. In the second phase, the demand for cruises was determined through the application of interviews. An annual average of 20 tourist boats and of 25,000 and 30,000 passengers was concluded; the demand of cruise tourism was analyzed through the application of questionnaires that determined the main motivations and the multivariate statistical analysis allowed identifying the potential segment, which is the 32% older adult, from the USA and Canada (32.1%) the survey was used. In the third phase the tourism and port offer was analyzed, highlighting the shortcomings of the (TPM) Manta port terminal, this being the deficiency in the tourist information provided within the facilities, the scarce tourist promotion by the agencies of trips focusing on the urban area of the city. As a last phase, a strategic analysis of cruise tourism was carried out, which allowed establishing commercial strategies for market introduction, advertising and personnel training, which will help boost cruise tourism as an important sector that generates foreign currency for the population in general.